Body Type, Self-Esteem and Assertiveness among High School Students in Ghana - Daniel Bruce (Centre for Behaviour and Wellness Advocacy, 2016)
The aim of this study was to examine the relationship between body type, self-esteem and assertiveness among adolescents of ages between 13 and 19 years. To achieve this aim, the study sampled 56 male and 94 female adolescents of the Senior High School in Accra, Ghana. Results showed that, higher self-esteem leads to assertiveness. Results also showed that body type perception affects self-esteem. It is, therefore, recommended that Guidance and Counselling officers in our schools should educate adolescent students on the three body types and the advantages associated with being one of these body types. This may help prevent developing body dysmorphic disorder, low self-esteem and non-assertiveness among students with negative perceptions of their body types and the possible effects on their personal relationships with peers, general academic performance and in- school and out-of- school life.